Estrategias didácticas para reforzar aprendizajes significativos a los estudiantes de segundo básica de la U.E. “Aurora Estrada y Ayala de Ramírez Pérez” Babahoyo-Los Ríos - Avilez Velasco, Jacqueline Yajaira (2023)
Didactic strategies play a vital role in student learning and teaching, because they develop skills and abilities throughout the educational process, so this work was carried out to investigate didactic strategies to reinforce significant and important learning in the subjects. taught by the teacher. The objective of this evidentiary research document was to identify didactic strategies to reinforce significant learning in second grade students, and thus establish strategies that benefit teaching in the classroom. The research work is field, the methods used are qualitative, quantitative, with a descriptive exploratory scope, where observation, survey and interview are the instruments that were applied for data collection through a sample comprised by a teacher. and 26 students of second grade parallel "A", obtaining as information for the analysis and interpretation of results, the work concludes that teachers must apply didactic strategies so that the teachings are interactive and innovative in the classroom, in the same way in this way, they must be trained to be updated in one way or another, and then provide the knowledge acquired in order to build meaningful learning in students.